The Effect of Animated Learning Media Using Powtoon on Student Learning Outcomes - Udin, Mukhammad Fahmi; Rezania, Vanda (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research was conducted to examine the impact of using Powtoon animated learning media on the learning outcomes of fifth-grade students in the subject of Social Studies at Muhammadiyah 5 Porong Elementary School, which previously had limited use of animation in the teaching process. The research method employed was quantitative research with a preexperimental design, specifically the one-group Pre-Test-Post-Test design. The subjects involved in this study were 17 fifth-grade students, selected using saturation sampling. Data collection was done through tests to measure the influence of implementing animated learning media on the learning outcomes of fifth-grade students, involving both a pre-test and a post-test consisting of a 20-item multiple-choice questionnaire. Data analysis was conducted using hypothesis testing, specifically the paired sample t-test, with a significance level of 0.000, indicating that the p-value was < 0.05. This result suggests a significant difference between the pre-test and post-test scores. Therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. Thus, it can be concluded that the use of animated learning media has a significant impact on student learning outcomes.